(NkOROLX rI^ARD TRETIJ(B: [(NpXESA(B] /s - (N{EKSPIR(B, (NuILXQMs ((NmOSKWA(B: s (NgOSUDARSTWENNOE IZDATELXSTWO HUDOVESTWENNOJ LITERATURY(B,s, 1958)
(Nw NASTOQ]EM IZDANII PREDSTAWLENA BESSMERTNAQ TRAGEDIQ u(B. (N{EKSPIRA (B"(NkOROLX rI^ARD TRETIJ(B".s
rus
Keywords: (NpXESYs; (NdRAMAs -- (NtRAGEDIQs